"Blessing gud ine " the lived experience of elderly celibate priests. - Rongcales, Natalio M. (Natalio M. Rongcales, 2018)
This study explored the lived experiences of elderly celibate priests (60 years old and above) and how it influenced their self-concept. Unstructured-interview was used to gather the data from 6 Waray elderly clerics. Interpretative Phenomenological Analysis (IPA) was used to interpret the lived experience of elderly priests because it is beneficial in discovering the hidden meaning of the participants' self-concept. Results showed that the self-concept of elderly celibate clerics has 3 main components: mind, body, and society. Our interpretation revealed that the lived experience celibacy of elderly clerics enhanced their self-concept because it gave them a sense of achievement after hurdling many struggles and eases with their lengthy practice. Strategies in managing their self-concept include reframing, legitimizing their practice, and social support system. Theoretical and practical implications are discussed on how the Church officials and families should support the practice of celibacy.
Undergraduate thesis (BA Psychology) -- University of the Philippines, Tacloban.